Accelerated aging of loose asphalt mixtures using ozone and other reactive oxygen species. (8th November 2021) - Sreeram, Anand; Masad, Ahmad; Sootodeh Nia, Zahra; Maschauer, Daniel; Mirwald, Johannes; Hofko, Bernhard; Bhasin, Amit
Highlights: A method for the accelerated aging of loose asphalt mixtures using ozone and other reactive oxygen species (ROS) was proposed in this study. Oxidation metrics studied include rheological parameters, FTIR analysis and SARA fractionation. ROS aging method showed similar or higher levels of aging just after 24 h compared to the conventional 5-day oven aging method. Results indicated that the ROS aging method could be promising approach towards the development of an accelerated aging protocol. Abstract: Efficient and practical techniques to simulate aging of asphalt mixtures is a focus area for practitioners around the world. In this study, a laboratory procedure was developed for accelerated aging of loose asphalt specimens using highly oxidative gas consisting of two types of reactive oxygen species (ROS) i.e., ozone (O3 ) and nitrogen oxides (NOx ). The procedure involved the aging of loose mixtures in an enclosed ROS rich environment for a period of 1 day at 95 °C. The chemical and rheological properties of the extracted binders from 5 different mixtures aged using this method were then compared to analogous binders aged using a benchmark of loose mixture aging at 95 °C for 5 days in a laboratory oven. Different metrics for oxidation and aging were comprehensively evaluated including extent of oxidative groups by Fourier transform infrared spectroscopy (FTIR), high and low temperature rheological properties using dynamic shear rheometer (DSR), and polarity based chemical fractionation into saturates, aromatics, resin and asphaltene (SARA) fractions. Favorable chemo-mechanical correlations were obtained from the results which confirmed that the mixtures aged using the ROS aging method showed similar or higher levels of aging just after 24 hrs when compared to the conventional 5-day aging method. Overall, the procedure developed serves as a proof of concept and provides encouraging results for further work towards the development and standardization of such an approach.